Determining Interday & Intraday Reliability of the 10/5 Repeated Jump Test in Elite Australian Footballers - Benjamin Southey; Mark Connick; Dirk Spits; Damien Austin; Emma Beckman (International Universities Strength and Conditioning Association, 2023)
The reactive strength index (RSI) measures the stretch shortening cycle (SSC), an important neuromuscular property for running performance, and critical for the game of Australian Football (AF). The 10/5 Repeated Jump test (RJ) is used to measure RSI, thus, the aims of the study were to determine if this test was reliable and could determine worthwhile change. Twenty-three male participants from an elite AF club completed RJ testing on two separate days of the week during the start of the preseason to determine interday and intraday reliability and determine whether smallest worthwhile change could be detected. All variables measured, (RSI, ground contact time, flight time, mean impulse and mean active stiffness) all had "excellent" ICC ratings >0.90 for both interday and intraday reliability. Mean landing RFD had "good" (ICC: 0.88) ratings for interday and "excellent" ratings for intraday reliability. Coefficient of variation ranged between 1.36-5.56% for all variables. All variables had a usefulness rating of "good", indicating ability to detect smallest worthwhile change. The RJ test, is a reliable and sensitive measure to assess reactive strength index in AF athletes.